Computability of the Emergency Service System Design Problem - Jaroslav Janacek; Ludmila Janosikova (Communications - Scientific letters of the University of Zilina, 2008)
The paper deals with emergency medical system design using methods of mathematical programming. The problem consists in optimal location of stations, where ambulance vehicles should be placed. Several possible objective functions are discussed and the relevant mathematical programming models are presented. The comparison of the solutions is reported based on the computational experiments in the conditions of the Slovak Republic.